579. LONG TERM RESULTS OF THE PULL-DOWN HELLER-DOR TECHNIQUE FOR ACHALASIA PATIENTS WITH SIGMOID ESOPHAGUS. (24th September 2022) - Tassi, Valentina; Lugaresi, Marialuisa; Daddi, Niccolò; Pilotti, Vladimiro; Mattioli, Benedetta; Bassi, Francesco; Mattioli, Sandro
Abstract: The outcome of achalasia treatment in patients with sigmoid esophagus is worse than that achieved for fusiform achalasia. We compared two groups of sigmoid achalasia patients, in which we performed the standard Heller-Dor procedure (HD) and the Heller-Dor plus a technique aimed to restore the vertical axis of the intraabdominal portion of the esophagus pull-down Heller-Dor (PD-HD). Long-term results were evaluated. We considered 48 patients affected by primitive esophageal sigmoid achalasia operated upon consecutively (1979-2021) in first instance. After 1987, we routinely isolated 360° of the gastro-esophageal junction and the lower esophagus and applied U stitches at the right side of the lower esophagus to pull down and rotate the gastro-esophageal junction toward the right. Twenty-five patients underwent the standard HD and 23 patients underwent the PD-HD technique. Postoperative follow-up included barium swallow, clinical interview investigating dysphagia and reflux symptoms and endoscopy. The overall outcome was graded from excellent to poor according to the severity of symptoms and esophagitis. The median follow-up period was 11 years (IQR 6-22) for HD group and 9 (IQR 6-14) for PD-HD (p=0.22). At postoperative barium swallow, patients in the PD-DH group had smaller esophageal diameter [4 cm (IQR 4-4.7) vs 4.7 cm (IQR 4-5), p=0.04] and lower residual barium column [10 cm (IQR 6-13) vs 6 cm (IQR 0-8), p=0.001] than those in the HD group. Postoperative moderate-severe (D2-D3) dysphagia rates were 40% for HD and 13% for PD-HD group (p=0.003). The outcome of treatment revealed satisfactory (excellent, good, fair) results in 68% and 91.4% of HD and PD-HD group patients, respectively. The Heller-Dor operation is effective in the presence of sigmoid achalasia. The clinical and instrumental evaluations showed better results with the PD-HD technique. This technique may be the first choice for end-stage achalasia with null or low risk for cancer.